PENGARUH SISTEM KEUANGAN DESA, SISTEM PENGENDALIAN INTERN PEMERINTAH, DAN TRANSPARANSI TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA (STUDI PADA DESA DI KABUPATEN ACEH TENGAH) - Nanda Sari; Jhon Andra Asmara (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
The purpose of this study was to examine the effect of the village financial system, government internal control, and transparency on the accountability of village fund management (study on villages in Kabupaten Aceh Tengah). This research is a quantitative research with a questionnaire used as primary data elicitation and interval scale as a measure. The research was conducted in Kabupaten Aceh Tengah. A total of 90 respondents were selected, consisting of Banta, Treasurer, and the head of budgeting. The sampling technique used purposive sampling. The data analysis technique used was multiple linear regression facilitated by SPSS version 25. The results showed that the variables of the village financial system, government internal control system, and transparency had a simultaneous effect on the accountability of village fund management. However, the results of the partial transparency research have no effect on the accountability of village fund management